Implementation of Augmented Reality Technology For Human Skeletons Learning Based on Android - alders paliling (Journal of Information Technology and Its Utilization, 2019)
One of the materials taught in science lesson is about human skeletons. In the learning process of the human skeletal, teachers use props in the form of human skeletal models. With the development of technology, the use of human skeletal models can be replaced with digital models. Human skeletal models can be damaged either by deliberate or accidentally by age. The correct method for replacing the model of a human skeleton into a digital form is by using Augmented Reality technology, where Augmented Reality technology is capable of projecting 3-dimensional objects into the real world directly. The use of augmented reality technology is increasingly prevalent in the world of education, health, sales, and tourism. The results obtained in this study was the application could project 3-dimensional objects from the human skeleton that was divided into 4 parts of the skull, spine and ribs, the bone of the upper tool and the bone of the motion of the bottom of the marker. Based on the tests that have been done, it was concluded that a good distance in identifying markers between smartphones with markers is at a distance between 2-6 inches and marker slope of the smartphone is 00-600